Simultaneous determination of bupropion, metroprolol, midazolam, phenacetin, omeprazole and tolbutamide in rat plasma by UPLC‐MS/MS and its application to cytochrome P450 activity study in rats. (13th January 2015) - Ma, Jianshe; Wang, Shuanghu; Zhang, Meiling; Zhang, Qingwei; Zhou, Yunfang; Lin, Chongliang; Lin, Guanyang; Wang, Xianqin
Abstract A specific ultra‐performance liquid chromatography tandem mass spectrometry method is described for the simultaneous determination of bupropion, metroprolol, midazolam, phenacetin, omeprazole and tolbutamide in rat plasma with diazepam as internal standard, which are the six probe drugs of the six cytochrome P450 isoforms CYP2B6, CYP2D6, CYP3A4, CYP1A2, CYP2C19 and CYP2C9. Plasma samples were protein precipitated with acetonitrile. The chromatographic separation was achieved using a UPLC® BEH C18 column (2.1 × 100 mm, 1.7 µm). The mobile phase consisted of acetonitrile and water (containing 0.1% formic acid) with gradient elution. The triple quadrupole mass spectrometric detection was operated by multiple reaction monitoring in positive electrospray ionization. The precisions were <13%, and the accuracy ranged from 93.3 to 110.4%. The extraction efficiency was >90.5%, and the matrix effects ranged from 84.3 to 114.2%. The calibration curves in plasma were linear in the range of 2–2000 ng/mL, with correlation coefficient (r2) >0.995. The method was successfully applied to pharmacokinetic studies of the six probe drugs of the six CYP450 isoforms and used to evaluate the effects of erlotinib on the activities of CYP2B6, CYP2D6, CYP3A4, CYP1A2, CYP2C19 and CYP2C9 in rats. Erlotinib may inhibit the activity of CYP2B6 and CYP3A4, and may induce CYP2C9 of rats. Copyright © 2015 John Wiley & Sons, Ltd.